Utilization rate of fish resources in Banggai Laut waters - Aswad Eka Putra (Gorontalo State University, 2020)
Capture fisheries is one of the leading sectors that drive the economy of Banggai Laut Regency. Improved fishing technology is related to fishing efforts that will affect the sustainability of fish resource stocks in the waters of Banggai Laut Regency. This study aims to identify the rate of utilization of fish resources in an effort to develop a sustainable fisheries sector in Banggai Laut waters. The method approach used is